Pengaruh Faktor Sosial Dalam Penyalahgunaan Narkoba di Kalangan Remaja Desa Pasir Permit - Widyanti, Sabilah; Samin Lubis, Mara; Sari Siregar, Hassya Gita; Hafsah Pane, Aulia; Haris Sembiring, Oscar; Sumitro, Dimas (PT. Alahyan Publisher Sukabumi, 2024)
Narcotics is an abbreviation for Narcotics, Psychotropics and other addictive substances. In 2023, drug users will show a prevalence rate of 1.73% or the equivalent of 3.3 million Indonesians aged 15-64 years. Some factors of drug abuse are the influence of parents, peers, knowledge, attitudes and beliefs. The aim of this research is to find out what social factors are related to drug abuse among teenagers in Pasir Permit Village. This type of research is qualitative based on socialization observations, discussions and questionnaires with 16 people filled in by teenagers from Pasir Permit village. The data shows that social factors influence family (13.3%), peer environment (40%), community environment (53.3%), mass media (6.7%) and living environment (13.3%) . The conclusion in this research is that community and peer relationships are very influential. So for teenagers, hanging out with peers who have positive behavior, and doing lots of positive activities will have a good impact on the future.